(Trans)esterification of mannose catalyzed by lipase B from Candida antarctica in an improved reaction medium using co-solvents and molecular sieve. - Nott, Katherine; Brognaux, Alison; Richard, Gaëtan; Laurent, Pascal; Favrelle, Audrey; Jérôme, Christine; Blecker, Christophe; Wathelet, Jean-Paul; Deleu, Magali (2012)
Four co-solvents (dimethylformamide [DMF], formamide, dimethyl sulfoxide [DMSO], and pyridine) were tested with tert-butanol (tBut) to optimize the initial rate (v₀) and yield of mannosyl myristate synthesis by esterification catalyzed by immobilized lipase B from Candida antarctica. Ten percent by volume of DMSO resulted in the best improvement of v₀ and 48-hr yield (respectively 115% and 13% relative gain compared to pure tBut). Use of molecular sieve (5% w/v) enhances the 48-hr yield (55% in tBut/DMSO [9:1, v/v]). Transesterification in tBut/DMSO (9:1, v/v) with vinyl myristate leads to further improvement of v₀ and 48-hr yield: a relative gain of 85% and 65%, respectively, without sieve and 25% and 10%, respectively, with sieve, compared to esterification. No difference in v₀ and 48-hr yield is observed when transesterification is carried out with or without sieve. info:eu-repo/semantics/published